The Mitotic Exit Network: Methods and Protocols - Monje-Casas, Fernando; Queralt, Ethel (Methods in molecular biology, 2017)
Regulation of Mitotic Exit in Saccharomyces cerevisiae -- Methods of Synchronization of Yeast Cells for the Analysis of Cell Cycle Progression -- Analysis of Cell Cycle Progression in Saccharomyces cerevisiae Using the Budding Index and Tubulin Staining -- Determination of Cell Cycle Stage and Mitotic Exit Through the Quantification of the Protein Levels of Known Mitotic Regulators -- Cdc14 Localization as a Marker for Mitotic Exit: In Vivo Quantitative Analysis of Cdc14 Release -- In Vitro Analysis of Tem1 GTPase Activity and Regulation by the Bfa1/Bub2 GAP -- Analysis of Protein-Protein Interactions Between MEN Components -- A New Methodology for the Quantification of In Vivo Cdc14 Phosphatase Activity -- Analysis of SUMOylation in the RENT Complex by Fusion to a SUMO-Specific Protease Domain -- A Substrate Trapping Method for Identification of Direct Cdc14 Phosphatase Targets -- Localizing MEN Components by Indirect Immunofluorescence Analysis of Budding Yeast -- Analysis of the Localization of MEN Components by Live Cell Imaging Microscopy -- Evaluation of the Dynamicity of Mitotic Exit Network and Spindle Position Checkpoint Components on Spindle Pole Bodies by Fluorescence Recovery After Photobleaching (FRAP) -- Asymmetric Localization of Components and Regulators of the Mitotic Exit Network at Spindle Pole Bodies -- Evaluation of the Nucleolar Localization of the RENT Complex to Ribosomal DNA by Chromatin Immunoprecipitation Assays -- Analysis of the Functionality of the Mitotic Checkpoints -- Cdc14 and Chromosome Condensation: Evaluation of the Recruitment of Condensin to Genomic Regions -- Studying the Role of the Mitotic Exit Network in Cytokinesis -- Hippo Signaling in Mitosis: An Updated View in Light of the MEN Pathway.